IMPLEMENTASI SAINTIFIK DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR NANGA PINOH - Mastura, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Scientific approach is a learning process that uses the process of scientific thinking. Implementing a scientific approach through thematic learning is necessary to make learners more interested in finding and building their own meaningful and joyfull knowledge. This study aimed to describe the thematic learning by using a scientific approach to the fourth grade in primary school Nanga Pinoh. This research is a descriptive research. The subjects were principals, classroom teachers, and students of fourth grade at Elementary School 1 Nanga Pinoh, Elementary School 06 Nanga Pinoh and Elementary Shcool Immanuel Christian Nanga Pinoh. Data collection techniques used were observation, interviews, and documentation. Analysis of the data by using the steps: data reduction, data display, and conclusion. Mechanical examination of the validity of data by using triangulation. The results showed that the fourth grade teachers have carried out thematic learning with a scientific approach. The scientific approach is implemented include : (1) observing, (2) questioning, (3) experimenting, (4) associating and (5) communicating/networking. With a scientific approach in thematic learning, learners become more active in learning, especially so confident and dare to ask, reason and express ideas or opinions, so as to obtain their knowledge performed by direct experience. Keywords : thematic learning, scientific approach